Life-Threatening Mediastinal Hematoma Formation After Removal of the Hemodialysis Catheter in a Boxer: A Case Report - Mitropoulou, Athanasia; Lehmann, Hendrik; Heier, Evelyn M.; Schneider, Matthias; Hassdenteufel, Esther (Frontiers in Veterinary Science, 2021)
A 4-year-old female Boxer was referred for renal replacement therapy two days after observed grape ingestion. An eleven-French dual-lumen dialysis catheter was placed into the right jugular vein and continuous renal replacement therapy was initiated for 66 hours. Afterwards the patient received enoxaparin subcutaneously as a thromboprophylaxis. Four hours after removal of the dialysis catheter the patient developed severe dyspnea with hypercapnia and signs of hemorrhagic shock. Bedside ultrasound and X-rays of the thorax revealed a soft tissue opacity dorsally of the trachea, located in the mediastinum. The findings were consistent with mediastinal bleeding and hematoma formation. Blood gas examination indicated hypoventilation. The dog was managed conservatively with multiple blood transfusions and mechanical ventilation. The patient survived to discharge, and the hematoma was fully absorbed in the radiographs after seventeen days. Patients with impaired kidney function should receive individualized enoxaparin dosage adjusted to anti-Xa levels and should be strictly monitored for complications. Mediastinal hemorrhage and hematoma formation should be considered as a potential complication in patients receiving a jugular vein catheter.